Factors Predicting Ineffectiveness of Conservative Treatment in Lumbar Disc Herniation in Patients Presenting to a Tertiary Care Hospital of Pakistan - Abbas, Amber; Shah, Irfan Ali; Ghori, Shiraz Ahmed; Jummani, Muhammad Mohsin; Jan, Muhammad Imran; Talreja, Vikash (Biological and Clinical Sciences Research Journal, 2025)
Conservative therapy is the first‑line approach for most patients with lumbar disc herniation (LDH), yet a substantial subset fail to improve and ultimately require invasive procedures. Identifying early predictors of conservative-treatment failure could optimize patient selection and allocation of limited resources in low- and middle-income settings. Objective: To determine the clinical, radiological, and treatment‑related factors associated with ineffective conservative management among patients with LDH presenting to the neurosurgical outpatient department of Dr Ruth Pfau Civil Hospital, Karachi. Methods: In this longitudinal study, 100 adults (18–60 years) with MRI‑confirmed LDH were enrolled over six months from August 2024 to January 2025 and followed for 24 weeks. Demographic data, comorbidities, symptom duration, neurological findings, and detailed MRI metrics were recorded on a pre-validated proforma. Conservative modalities (pharmacological, physiotherapeutic, and interventional) were documented prospectively. Treatment outcome at week 24 was dichotomised as effective (complete/partial relief) or ineffective (no relief). Multivariable logistic regression was used to explore independent predictors of ineffectiveness. Results: Overall, 27% of patients experienced no symptomatic relief despite standard conservative care. Hypertension (adjusted OR 2.48, 95% CI 0.83–7.37), paracentral herniation (OR 1.55, 95% CI 0.54–4.47), and baseline canal compromise ≥40 % (OR 1.42 per 10 % increase) showed a trend towards treatment failure, whereas structured physiotherapy conferred a non‑significant protective effect (OR 0.48, 95% CI 0.18–1.29). Conclusion: Failure of conservative therapy in LDH is multifactorial and appears more frequent in hypertensive patients and those with severe canal compromise or paracentral fragments. Early risk stratification may help direct such patients to expedited surgical review, potentially shortening disability time in resource‑constrained Pakistani settings.